HUBUNGAN KOMUNIKASI INTERPERSONAL DAN KOMITMEN TERHADAP ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA III (PERSERO) - Sarinah, Sarinah; Aziz, Azhar (Universitas Medan Area, 2010)
This study aims to determine the relationship of interpersonal communication and organizational commitment to employee job satisfaction. The hypothesis in this study were: